MODERN STATE AND OBJECTIVE CHARACTERISTICS OF PROFESSIONAL CULTURE OF THE MANAGER OF INTERNATIONAL TOURISM - Lukianets, Alla (Educological discourse, 2019)
Tourism development is one of the most promising ways out of the economic crisis. Thanks to tourism, many countries have achieved significant improvements in the rates of economic development and livelihoods. Ukrainian citizens are peculiar investors of foreign countries, which is one of the most painful issues in the domestic tourism industry. According to the State Statistics Committee of Ukraine, in 2000, the number of Ukrainian citizens who traveled abroad was 13422320 people, while in 2017 this number increased to 26437413 people. The number of foreigners who visited Ukraine in 2017 increased significantly, compared with 2000. However, the peak of tourists fell in 2008 (25449078 people). In addition to the situation in the country in the field of tourism, an important component in the functioning of the tourism business is the personnel, namely the professional culture of the tourism manager. Professional activity, as a category of culture, encompasses not only its productive component, but also information. The culture of professional activity is a set of basic professional knowledge, skills and abilities, readiness for the construction and solution of innovative tasks, practical experience, nonlinear thinking, as well as the steady ownership of information technologies. In general, it can be noted that the professional culture of the manager of international tourism includes such components as: professional outlook, professional behavior, professional skills. The world-famous concept of a specialist is based on the principles of humanism, universal morality, respect for people, involves a combination of the value orientation of a person of an open society with patriotism. With regard to professional behavior, the main thing for the manager of international tourism in this regard is the communicative culture, as the ability to communicate with people most valuable in the field, where the main is personal contact, communicative culture is a prerequisite for the effective functioning of professional activity.